2021
DOI: 10.1177/0897190021997008
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation and Effect of Weekend Pharmacy-Driven Antimicrobial Stewardship Services at a Large Academic Medical Center

Abstract: Background: In September 2018, pharmacy antimicrobial stewardship (AMS) services were expanded to include weekends at this academic medical center. Activities performed by AMS pharmacists on the weekends include blood culture rapid diagnostic (RDT) review, antiretroviral therapy (ART) review, prospective audit and feedback (PAF) utilizing clinical decision support, vancomycin dosing, and operational support. The purpose of this study was to assess the operational and clinical impact of these expanded AMS servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Previous reports also showed that time to antibiotic tailoring and responses to culture results were slower outside working hours [ 25 , 26 ]. Bohn and colleagues expanded antimicrobial stewardship service to include weekends at a medical center and significantly reduced the time to resolution of antimicrobial stewardship opportunities [ 27 ]. Our results demonstrated that an active-delivery CDSS could remarkably decrease TAAT during off hours without increasing any workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports also showed that time to antibiotic tailoring and responses to culture results were slower outside working hours [ 25 , 26 ]. Bohn and colleagues expanded antimicrobial stewardship service to include weekends at a medical center and significantly reduced the time to resolution of antimicrobial stewardship opportunities [ 27 ]. Our results demonstrated that an active-delivery CDSS could remarkably decrease TAAT during off hours without increasing any workforce.…”
Section: Discussionmentioning
confidence: 99%
“…5 For example, when pharmacy-driven antimicrobial stewardship services were expanded to weekends in a cohort of medicine patients, a decreased time to both escalation and de-escalation of antimicrobials was achieved. 10 Studies assessing the impact of expanding emergency department pharmacy services to 24 hours have reported decreased medication errors, improvement in medication reconciliations, improved staff satisfaction, and increased cost savings. 11,12 Multiple studies have also demonstrated improved perceptions of quality of care when evening shift pharmacist are included.…”
Section: Introductionmentioning
confidence: 99%